Interprofessional collaboration within Canadian integrative healthcare clinics: Mixing oil and water - Gaboury, Isabelle (University of Ottawa (Canada), 2009)
Integrative healthcare (IHC), the combination of biomedical disciplines and expertise in various forms of complementary and alternative medicine (CAM), is an example of interdisciplinary collaboration that has emerged over the last two decades. Little has been written so far to gain an understanding of how the healthcare practitioners in such setting collaborate. The main goal of this doctoral dissertation was to better understand what is inside the "black box" of interdisciplinary collaboration within IHC clinics so that appropriate links related to clinic effectiveness and cost-effectiveness as well as patient outcomes could be tested in future research. This thesis explored the concept of interprofessional collaboration in IHC using three theoretical and conceptual models: Input Process Output, Relationship-Centered Care, and Models of Team Healthcare Practice. Inductive and deductive inquiries were conducted through sequential mixed methods and methodological triangulation techniques. Four objectives were proposed to better understand how collaboration was experienced and conceptualized within these clinics and how the related factors interacted with each others. Finally, assumptions of a conceptual model of classification of IHC clinics were tested. Constructs contributing to collaboration included practitioners' attitudes and educational background, as well as external factors such as the healthcare system and financial pressures. Major processes affecting collaboration consisted in communication, patient referral and power relationships. These determinants of collaboration resulted in learning opportunities for practitioners, modified burden of work and ultimately, higher affective commitment toward the clinic. The quantitative inquiry revealed that interpersonal relationships were shown to be central to the collaborative practice of IHC delivery. Additionally, beliefs in the benefits of collaboration were found to play an important role in an IHC collaborative enterprise. Finally, clinic model comparisons confirmed that interprofessional collaboration is modulated by the practice model. Suggestions to improve the conceptual model of classification were made. This multi-method study was the first to summarize systematically the factors that impact and ensue from interprofessional collaboration in the context of Canadian IHC. The framework lay down by this dissertation represents an important step to investigate further the impact of IHC on patients and the Canadian healthcare system and to guide the development of more effective IHC clinics.
Keywords: Health Sciences, Alternative Medicine.; Health Sciences, Health Care Management.